Water absorption and salt attack resistance of coal ash brick made of different percentage of foam content - Ismail, Sushilawati (2014)
Coal ash which constitute of fly ash and bottom ash were proved to be used as main component in brick production. However, published work on the coal ash brick with addition of foam in order to produce lightweight brick is still lacking. This thesis reports the effect of variation in foam content in coal ash brick on the density, water absorption and salt attack resistance. Comparison of those parameters was made between the coal ash bricks and conventional brick. The coal ash brick mixes were formulated using industrial by-product, ground granulated blastfurnace slag (GGBS) which is activated with an alkaline (hydrated lime or Portland cement) combined with coal ash from coal-fired thermal power plant. The blended binder comprising of hydrated lime (HL) – GGBS and Portland cement (PC) –GGBS were used to stabilize the coal ash brick. Foam was used to produce lightweight brick. The percentage of foam added to the brick mixes are 25%, 50% and 75%. A total of sixty (60) brick specimen subjected to ten (10) series of mix proportion were cast and put in air curing condition for at least 28 days before testing. The density measurement in accordance with AS/NZS 4456.8, water absorption test in accordance with BS EN 772-21 and salt attack resistance in accordance with AS/NZS 4456.10 were evaluated on the brick specimens. The results indicated that the density of coal ash brick decreases with the increase in foam content. Also for bricks composed of both blended binder, the water absorption were directly proportional to the amount of foam. Thus, the water absorption of foam brick increases with the reduction in density. Higher foam content leads increase of pores and capillaries in brick structure, therefore the brick become weaker to resist on salt attack. XRD pattern of formed brick with 75% of foam addition on HL-GGBS coal ash brick portrays ettringite formation were attributed to disruption of brick structure. The use of coal ash with HL–GGBS and PC-GGBS combination as binder agent has been observed to be lightweight, low in water absorption, and advantageous in protection to salt attack compare to the conventional brick. The optimum proportion respected to the foam content is 50% in balance condition with approximately 1-2% of mass loss due to salt attack, 12-13% of water absorption and density significantly reduced to 1600kg/m3 . Keywords – fly ash; bottom ash; hydrated lime; Portland cement; ground granulated blastfurnace slag (GGBS); foam; brick; density; water absorption; salt attack resistance